2004
DOI: 10.1128/jcm.42.1.140-145.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Human Herpesvirus 6 Infection by a Novel DNA Amplification Method, Loop-Mediated Isothermal Amplification

Abstract: A novel nucleic acid amplification method, termed loop-mediated isothermal amplification (LAMP), which amplifies DNA with high specificity, efficiency, and rapidity under isothermal conditions, may be a valuable tool for the rapid detection of infectious agents. LAMP was developed for human herpesvirus 6 (HHV-6), and its reliability was evaluated in this study. Although LAMP products were detected in HHV-6 B and HHV-6 A DNA, they were not detected in HHV-7 and human cytomegalovirus DNA. The sensitivity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 31 publications
2
57
0
1
Order By: Relevance
“…LAMP has been used to detect many kinds of virus infection, mainly for DNA virus or bacterial genome infection (4,6,10,11). Recently, RT-LAMP was used to detect West Nile virus (17).…”
Section: Discussionmentioning
confidence: 99%
“…LAMP has been used to detect many kinds of virus infection, mainly for DNA virus or bacterial genome infection (4,6,10,11). Recently, RT-LAMP was used to detect West Nile virus (17).…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for the development of sensitive, simple, costeffective, and rapid diagnostic techniques for HCV detection. In 2000, Notomi et al [17] reported a novel nucleic acid amplification method, termed the loop-mediated isothermal amplification (LAMP), that amplifies target sequences with high specificity, efficiency, and speed under isothermal conditions [5,10]. The only equipment needed for the LAMP reaction is a regular laboratory water bath or a heat block that furnishes a constant temperature of 62-65°C [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This method also exhibits extremely high amplification efficiency, due in part to its isothermal nature; as there is no time lost due to changes in temperature and the reaction can be conducted at the optimal temperature for enzyme function, the inhibition reactions that often occur at later stages of typical PCR amplifications are less likely to occur. Thus, this method could potentially be a valuable tool for the rapid diagnosis of infectious diseases (5,8,9,12,19,23) in both commercial and hospital laboratories. In this study, we sought to establish a LAMP-based HSV typespecific DNA amplification method and examine its reliability for the detection of HSV DNA from clinical specimens.…”
mentioning
confidence: 99%